A wear-resistant flame-retardant cloth wire and a preparation method thereof

CN122455468BActive Publication Date: 2026-10-27HUNAN HUALITONG CABLE
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610770277.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-06-01
Publication Date
2026-10-27
Estimated Expiration
2046-06-01

AI Technical Summary

Technical Problem

现有交联聚乙烯基布电线绝缘层依然存在阻燃性、耐磨性、耐开裂性和耐低温性较差的问题

Benefits of technology

本发明提供了一种耐磨阻燃布电线及其制备方法,本发明通过以下方法同时提高了交联聚乙烯基布电线绝缘层的阻燃性、耐磨性、耐开裂性和耐低温性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a wear-resistant and flame-retardant cloth wire and a preparation method thereof, and relates to the technical field of power cables. The application comprises a copper conductor and an insulation layer. The insulation layer is made of mixing materials, and the mixing materials comprise the following raw materials in mass parts: 1000-1100g parts of wear-resistant and toughening masterbatch, 3-3.4 parts of p-hydroxyanisole, 160-175 parts of flame-retardant crosslinking agent, 12-13 parts of photoinitiator 184, and 12-13 parts of benzophenone. The wear-resistant and toughening masterbatch comprises the following raw materials: high-density polyethylene resin, antioxidant 1010, antioxidant 168, dilauryl thiodipropionate, synergistic microspheres, crosslinking aid, and hydroxymethylpropane trimethyl acrylate. In the application, the introduction of the flame-retardant crosslinking agent, the synergistic microspheres and other raw materials effectively improves the flame retardance, wear resistance, crack resistance and low-temperature resistance of the crosslinked polyethylene-based insulation layer. Therefore, the application has a more extensive application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of power cable technology, specifically to a wear-resistant and flame-retardant fabric wire and its preparation method. Background Technology

[0002] Building electrical cables are core products for low-voltage fixed wiring with a rated voltage of 450 / 750V and below. They are indispensable key components in low-voltage power supply systems such as civil buildings, home electrical installations, public facilities, and industrial auxiliary power supply. The performance of their insulation layer directly determines the long-term safety and operational stability of the power supply system. Cross-linked polyethylene (XLPE), with its excellent electrical insulation properties, higher long-term operating temperature resistance, greater current carrying capacity, and excellent anti-aging characteristics, has become the mainstream matrix material for building electrical cable insulation layers and is being widely used in various building and engineering scenarios.

[0003] However, in practical engineering applications, the cross-linked polyethylene (XLPE) fabric wire insulation layer still has the following core performance shortcomings: First, XLPE is a hydrocarbon polymer with an extremely low oxygen index, making it highly flammable. Furthermore, the combustion process is accompanied by severe dripping, which can easily cause secondary flame spread. Second, during long-term conduit installation, bending construction, and daily use, the XLPE insulation layer exhibits insufficient abrasion resistance and poor resistance to environmental stress cracking, easily leading to insulation wear and micro-cracks due to friction and environmental stress. Therefore, the flame retardancy, abrasion resistance, crack resistance, and low-temperature resistance of existing XLPE fabric wires still need improvement. Summary of the Invention

[0004] The purpose of this invention is to provide a wear-resistant and flame-retardant electrical wire and its preparation method, thereby solving the following technical problems: Existing cross-linked polyethylene-based fabric wire insulation layers still suffer from poor flame retardancy, abrasion resistance, crack resistance, and low-temperature resistance.

[0005] The objective of this invention can be achieved through the following technical solutions: A wear-resistant and flame-retardant cloth wire, comprising a copper conductor and an insulation layer; The insulating layer is made of a compound, which includes the following raw materials in parts by weight: 1000-1100 g of wear-resistant and toughening masterbatch, 3-3.4 g of p-hydroxyanisole, 160-175 g of flame-retardant crosslinking agent, 12-13 g of photoinitiator 184, and 12-13 g of benzophenone. The wear-resistant and toughening masterbatch comprises the following raw materials in parts by weight: 1000-1100 parts of high-density polyethylene resin, 5-5.5 parts of antioxidant 1010, 2-2.2 parts of antioxidant 168, 2-2.2 parts of dilauryl thiodipropionate, 60-66 parts of synergistic microspheres, 9-10 parts of crosslinking aid, and 9-10 parts of hydroxymethylpropane trimethacrylate; The flame retardant crosslinking agent is prepared from hexachlorocyclotriphosphazene, allyl alcohol, triethylamine, hydroxyethyl methacrylate, 4-dimethylaminopyridine, and p-hydroxyanisole. The enhanced microspheres are prepared by first modifying nano-silica with vinyltrimethoxysilane and 3-methacryloyloxypropyltrimethoxysilane, and then reacting it with maleic anhydride-grafted polyethylene wax and vinyl-terminated polydimethylsiloxane under the initiation of benzoyl peroxide.

[0006] Preferably, the flame retardant crosslinking agent is prepared by the following method: Hexachlorocyclotriphosphazene was dissolved in anhydrous tetrahydrofuran 1, and then a mixed solution of allyl alcohol and triethylamine 1 was added dropwise under a nitrogen atmosphere at -5-0℃. The reaction was carried out at 0℃ for 6 hours, then filtered and the filtrate was subjected to vacuum distillation (to remove the solvent and excess allyl alcohol). Subsequently, it was dissolved in anhydrous tetrahydrofuran 2, and then hydroxyethyl methacrylate, 4-dimethylaminopyridine, triethylamine 2, and p-hydroxyanisole were added under a nitrogen atmosphere. The reaction was carried out at 30℃ in the dark for 18-20 hours. After filtration, the filtrate was subjected to vacuum distillation to remove the solvent. Finally, it was recrystallized and dried to obtain the flame retardant crosslinking agent.

[0007] Preferably, the ratio of hexachlorocyclotriphosphazene, anhydrous tetrahydrofuran 1, allyl alcohol, triethylamine 1, anhydrous tetrahydrofuran 2, hydroxyethyl methacrylate, 4-dimethylaminopyridine, triethylamine 2, and p-hydroxyanisole is 347.65g: 500-550mL: 174g: 334g: 500mL: 390.42g: 14.66g: 334g: 7.45g.

[0008] Preferably, the method for preparing the synergistic microspheres is as follows: A1: After vacuum drying, nano-silica is dispersed in anhydrous toluene. Under nitrogen atmosphere, it is ultrasonically dispersed and then vinyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, deionized water, and glacial acetic acid are added and stirred for 20-30 min. Then, it is refluxed at 110℃ for 6-7 h (the reflux device is equipped with a water separator to continuously separate the methanol and water generated in the reaction). After centrifugation, it is washed 3-5 times with anhydrous toluene and vacuum dried to obtain modified silica. A2: Dissolve benzoyl peroxide in anhydrous toluene to obtain a benzoyl peroxide solution; A3: Maleic anhydride-grafted polyethylene wax and vinyl-terminated polydimethylsiloxane were dissolved in anhydrous toluene and ultrasonically dispersed at 75°C under a nitrogen atmosphere. Then, the temperature was raised to 80°C and benzoyl peroxide solution 1 was added dropwise. After reacting at 80°C for 4-5 hours, modified silica was added, followed by the addition of benzoyl peroxide solution 2 and reflux reaction for 8 hours. Finally, the mixture was centrifuged, washed, and dried to obtain enhanced microspheres.

[0009] Preferably, the ratio of nano-silica, anhydrous toluene, vinyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, deionized water, and glacial acetic acid in A1 is 100g:1000-1100mL:12g:8g:1mL:0.5mL.

[0010] Preferably, the mass ratio of benzoyl peroxide to anhydrous toluene in A2 is 2.5:7.5-12.5.

[0011] Preferably, the ratio of maleic anhydride-grafted polyethylene wax, vinyl-terminated polydimethylsiloxane, anhydrous toluene, benzoyl peroxide solution 1, modified silica, and benzoyl peroxide solution 2 in A3 is 40g:30g:800mL:6-9g:50g:4-6g.

[0012] A method for preparing a wear-resistant and flame-retardant electrical wire includes the following steps: S1: After vacuum drying of high-density polyethylene resin, it is mixed with antioxidant 1010, antioxidant 168 and dilauryl thiodipropionate for 3-5 minutes. Then, synergistic microspheres and crosslinking aids are added and mixed for 2 minutes. Subsequently, it is added to a twin-screw extruder and hydroxymethyl propane trimethacrylate is added in the second zone. Then, it is melt-extruded under vacuum conditions. Finally, it is water-cooled and pelletized to obtain wear-resistant and toughened masterbatch. S2: Under a light-proof, nitrogen atmosphere, wear-resistant and toughening masterbatch and p-hydroxyanisole are added to the main feed port of the twin-screw extruder, flame retardant crosslinking agent is added from the side feed zone 1, photoinitiator 184 and benzophenone are added from the side feed zone 2, then melt extrusion is carried out, and finally water cooling and pelletizing are performed to obtain the compound. S3: After vacuum drying of the compound, it is extruded and coated onto the surface of the copper conductor under vacuum and light-proof conditions. After cooling and shaping, it is preheated in a 60℃ preheating tunnel for 15 minutes, then irradiated. Finally, it is vacuum treated at 60℃ for 12-14 hours, then vacuum treated at 80℃ for 48-50 hours. After cooling, wear-resistant and flame-retardant wire is obtained.

[0013] Preferably, the crosslinking aid in S1 is either pentaerythritol tetraacrylate or dipentaerythritol hexaacrylate.

[0014] Preferably, the irradiation treatment in S3 is as follows: the device is placed on the conveyor belt of the electron beam irradiation equipment and subjected to an accelerating voltage of 1.5 MeV, an irradiation dose of 120 kGy, a conveyor belt speed of 0.5 cm / s, and irradiation on both sides four times.

[0015] The beneficial effects of this invention are: This invention provides a wear-resistant and flame-retardant cloth wire and its preparation method. The invention improves the flame retardancy, wear resistance, crack resistance and low temperature resistance of the cross-linked polyethylene cloth wire insulation layer through the following method.

[0016] (1) During combustion, the phosphorus-oxygen-carbon bond of the flame retardant crosslinking agent of the present invention is preferentially broken by heat, generating a phosphoric acid intermediate and further dehydrating and condensing to form polyphosphoric acid; polyphosphoric acid can synergistically work with the silicon-based components in the system, and act as an efficient dehydration and carbonization catalyst to promote the crosslinking of carbon-containing free radicals into char during combustion, significantly improving the char residue rate; phosphorus-oxygen free radicals can capture hydroxyl and hydrogen active free radicals in the combustion chain reaction and terminate the combustion chain reaction, which is the core flame retardant path of the system; under high temperature conditions in the later stage of combustion, the phosphorus-nitrogen bond of the phosphazene ring breaks, releasing inert gases such as nitrogen, diluting the concentration of combustible hydrocarbons and oxygen in the gas phase, and helping to suppress the spread of combustion.

[0017] The flame retardant crosslinking agent is a hexasubstituted polyfunctional reactive compound with cyclotriphosphazene as its core. The molecule contains both allyl and methacrylate unsaturated double bonds. The free radical polymerization activity of the methacrylate double bond is significantly higher than that of the allyl double bond. It can participate efficiently in the crosslinking reaction of high-density polyethylene under irradiation conditions to form a complete three-dimensional network with higher crosslinking density. This greatly improves the high-temperature melt strength of high-density polyethylene, inhibits melt flow and dripping during combustion, and solves the common dripping ignition problem in polyolefin flame retardants.

[0018] Irradiation crosslinking forms irreversible covalent bonds between molecular chains, which can effectively limit the slippage, deentanglement, and creep of molecular chains under frictional loads, reduce the shedding of surface materials, and decrease wear. Within a moderate crosslinking range, it can improve the surface hardness and elastic modulus of high-density polyethylene, reduce the actual contact area of ​​friction, and lower the probability of adhesive wear. At the same time, the unsaturated groups of the flame-retardant crosslinking agent can undergo free radical copolymerization with the vinyl groups on the surface of the enhanced microspheres, anchoring the enhanced microspheres in the crosslinking network through chemical bonds, significantly enhancing the interfacial bonding strength between nano-silica and the high-density polyethylene matrix, and reducing the risk of microsphere peeling and forming abrasive particles during friction.

[0019] The three-dimensional network formed by cross-linking can connect the high-density polyethylene macromolecular chains through covalent bonds, significantly improving the material's resistance to environmental stress cracking: covalent cross-linking restricts the slippage of molecular chains and slows down the cracking process; the cross-linking network can effectively disperse the concentrated stress at the tip of the notch, passivate the tip of the crater, limit the expansion of craters to the microscale range, prevent a single crater from rapidly penetrating the sample, and prolong the cracking time; the cross-linking effect can refine the spherulite size of high-density polyethylene, reduce the continuity of the crystalline region, reduce the stress concentration weak points at the spherulite interface, and slow down the rapid expansion of craters along the grain boundaries.

[0020] After appropriate crosslinking, the three-dimensional crosslinked network can disperse the concentrated stress at the notch tip to a wider area of ​​the matrix, inducing numerous micro-silver streaks and shear bands, thus efficiently absorbing impact energy. The alkyl structure of the side chain in the flame retardant crosslinking agent can introduce a certain structural relaxation capability into the crosslinked network, mitigating to some extent the increase in crosslinked network rigidity caused by the rigid phosphazene core and preventing a sharp increase in material brittleness after crosslinking. At the same time, the synergistic microspheres introduced through chemical bonds can serve as stable stress concentration points, inducing more micro-silver streaks and synergistically improving the impact strength of the material.

[0021] Crosslinking reduces the crystallinity of high-density polyethylene, refines spherulite size, and reduces stress concentration weak points at grain boundaries. Simultaneously, the crosslinking network weakens the binding of amorphous segments by crystalline regions, helping to maintain the mobility of amorphous segments at low temperatures and preventing low-temperature embrittlement of the matrix. The three-dimensional covalent network effectively disperses stress and passivates craze tips at low temperatures, delaying the rapid instability and propagation of crazes. Furthermore, flexible polydimethylsiloxane segments on the surface of the enhanced microspheres can be fixed in the matrix through chemical bonds. Polydimethylsiloxane maintains a highly elastic state at -40℃, forming numerous nanoscale flexible toughening microdomains in the matrix, further improving the material's low-temperature impact resistance.

[0022] (2) The enhanced microspheres prepared in this invention are organic-inorganic composite particles with vinylsilane-modified nano-silica as the core and polyethylene wax-g-polydimethylsiloxane copolymer as the grafted shell. The vinyl groups on the surface of the core form stable covalent bonds with the shell polymer through free radical grafting reaction, which can effectively inhibit the primary aggregation of nano-silica and improve its dispersibility in the polyolefin matrix. The polyethylene segments in the shell have excellent compatibility with the high-density polyethylene matrix, and the polydimethylsiloxane segments can give the material low friction characteristics and flexibility. The unsaturated double bonds remaining on the surface of the microspheres can undergo free radical copolymerization with the molecular chains of the high-density polyethylene matrix and the unsaturated groups of the flame retardant crosslinking agent during the subsequent irradiation crosslinking process, anchoring the inorganic composite particles in the three-dimensional crosslinking network of polyolefin through covalent bonds, which greatly enhances the interfacial bonding strength between the inorganic filler and the matrix.

[0023] The nano-silica in the enhanced microspheres and polydimethylsiloxane thermally decompose to generate amorphous silica during combustion, which can enhance the thermal stability and mechanical strength of the char layer. It also forms a stable phosphate glass phase with polymetaphosphoric acid generated by phosphazene flame retardant, which significantly improves the density and oxidation resistance of the char residue and forms a more stable physical barrier layer to isolate the transfer of oxygen, heat and combustible small molecules. At the same time, rigid nano-silica can increase the high-temperature melt viscosity of high-density polyethylene, and the grafted shell participates in cross-linking to form a complete network. The two work together to inhibit melt flow and dripping during combustion.

[0024] The nano-silica core significantly enhances the surface hardness and resistance to plastic deformation of the material, reducing direct contact between the matrix and the friction pair during friction and inhibiting adhesive wear and abrasive wear. The silica forms a strong interfacial bond with the matrix through covalent grafting of the shell and irradiation crosslinking anchoring, making it difficult to peel off and form abrasive particles during friction. The polydimethylsiloxane in the shell reduces the overall coefficient of friction, decreases shear force and frictional temperature rise at the friction interface, and prevents accelerated wear caused by matrix softening at high temperatures. Residual double bonds in the shell participate in irradiation crosslinking, increasing the overall crosslinking density of the matrix and limiting the slippage and creep of high-density polyethylene molecular chains. This prevents large-area material detachment due to matrix plastic deformation during long-term friction, improving the long-term stability of wear resistance.

[0025] The enhanced microspheres participate in the radiation crosslinking of high-density polyethylene (HDPE) through shell double bonds, making them rigid crosslinking nodes in a three-dimensional crosslinking network. This not only increases the overall crosslinking density but also stabilizes nano-silica within the network through covalent bonds, forming a rigid node-flexible segment crosslinking network. This restricts the slippage of HDPE molecular chains and enhances the material's resistance to environmental stress cracking. Under stress, the uniformly dispersed microspheres act as submicron-level stress concentration points, inducing a large number of uniformly distributed microcrazing and shear bands in the surrounding matrix, consuming stress energy and preventing the rapid instability and propagation of a single main craze. The flexible segments in the shell provide a certain deformation buffer at the craze tip region, helping to passivate stress concentration and prevent crazes from transforming into macroscopic cracks.

[0026] Under impact loads, uniformly dispersed rigid nano-silica cores act as submicron-level stress concentration points, inducing numerous fine microcracks and shear bands in the surrounding matrix. This efficiently dissipates impact energy, preventing energy concentration on a single crack and thus avoiding instantaneous fracture. When crack propagation encounters microspheres, the rigid silica core hinders the linear propagation of the crack, forcing it to deflect and diffract, extending the crack propagation path and further consuming impact energy. The polyethylene segments in the shell have good compatibility and modulus matching with the high-density polyethylene matrix. Combined with the strong interfacial effect of covalent bonding, this ensures effective transfer of impact stress, preventing brittle fracture directly caused by rigid particles. Simultaneously, the introduction of microspheres and appropriate irradiation crosslinking refines the spherulite size of high-density polyethylene, reduces crystallinity, and increases the proportion of amorphous regions capable of absorbing impact energy. The crosslinked network also contributes to the uniform transfer of impact energy, preventing localized stress concentration.

[0027] The polydimethylsiloxane in the shell remains in a highly elastic state at -40℃. Under low-temperature impact, it can absorb a large amount of impact energy through local deformation, while passivating the stress concentration at the crack tip and preventing the rapid propagation of cracks, effectively alleviating the low-temperature brittleness of high-density polyethylene. The moderately cross-linked network formed by the participation of microspheres can restrict the regular arrangement of high-density polyethylene molecular chains, reduce crystallinity, refine the size of spherulites, reduce grain boundary stress concentration points, and weaken the binding of the crystalline region to the chain segments in the amorphous region. This helps to maintain the mobility of chain segments at low temperatures and avoid complete embrittlement of the matrix.

[0028] Of course, any product implementing this invention does not necessarily need to achieve all of the advantages described above at the same time. Detailed Implementation

[0029] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. The embodiments described below are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0030] Unless otherwise specified, the following information pertains to some of the raw materials used in the following embodiments and comparative examples of this invention: Maleic anhydride-grafted polyethylene wax (molecular weight 3000-8000, grafting rate 1.2%-2.0%) was purchased from Qingdao Sainuo Chemical Co., Ltd.; vinyl-terminated polydimethylsiloxane (molecular weight 5000-8000) was purchased from Guangdong Wengjiang Chemical Reagent Co., Ltd.; high-density polyethylene resin was purchased from Dongguan Suyu Chemical Co., Ltd., brand name: DGDA3485.

[0031] Example 1: A method for preparing a wear-resistant and flame-retardant fabric wire is as follows: S1: Dissolve 347.65 g of hexachlorocyclotriphosphazene in 500 mL of anhydrous tetrahydrofuran. Then, under a nitrogen atmosphere at -5 °C, add a mixed solution of 174 g of allyl alcohol and 334 g of triethylamine dropwise (over 2 hours). React at 0 °C for 6 hours. Filter the solution and distill it under reduced pressure at 25 °C and -0.095 MPa (to remove the solvent and excess allyl alcohol). Then, redissolve the solution in 500 mL of anhydrous tetrahydrofuran. Under a nitrogen atmosphere, add 390.42 g of hydroxyethyl methacrylate and 14.66 g of triethylamine. 4-Dimethylaminopyridine, 334g triethylamine, and 7.45g p-hydroxyanisole were reacted at 30°C in the dark for 180h. After filtration, the solvent was removed by vacuum distillation at 30°C and -0.098MPa. Finally, the mixture was recrystallized three times at 0°C with a mixture of dichloromethane and methanol (volume ratio 10:1) and dried under vacuum at 30°C for 24h to obtain a flame retardant crosslinking agent. S2: 100g of nano-silica was vacuum dried for 12h and then dispersed in 1000mL of anhydrous toluene. After ultrasonic dispersion for 30min under nitrogen atmosphere, 12g of vinyltrimethoxysilane, 8g of 3-methacryloyloxypropyltrimethoxysilane, 1mL of deionized water, and 0.5mL of glacial acetic acid were added and stirred for 20min. Then, the mixture was refluxed at 110℃ for 6h (the reflux device was equipped with a water separator to continuously separate the methanol and water generated in the reaction). After centrifugation, the mixture was washed 3 times with anhydrous toluene and vacuum dried to obtain modified silica. S3: Dissolve 2.5g of benzoyl peroxide in 7.5g of anhydrous toluene to obtain a benzoyl peroxide solution; S4: 40g of maleic anhydride-grafted polyethylene wax and 30g of vinyl-terminated polydimethylsiloxane were dissolved in 800mL of anhydrous toluene and ultrasonically dispersed at 75℃ under a nitrogen atmosphere for 30min. Then, the temperature was raised to 80℃ and 6g of benzoyl peroxide solution was added dropwise at 0.2g / h. After reacting at 80℃ for 4h, 50g of modified silica was added, and then 4g of benzoyl peroxide solution was added dropwise at 0.1g / h and refluxed for 8h. After centrifugation and washing three times with hot toluene, the mixture was vacuum dried to obtain the enhanced microspheres. S5: 1000g of high-density polyethylene resin was vacuum dried at 80℃ for 4h, then mixed with 5g of antioxidant 1010, 2g of antioxidant 168 and 2g of dilauryl thiodipropionate at 3000r / min for 3min. Then, 60g of synergistic microspheres and 9g of pentaerythritol tetraacrylate were added and the mixture was continued to be kneaded for 2min. The mixture was then fed into a twin-screw extruder, and 9g of hydroxymethylpropane trimethacrylate was added in zone two. The mixture was then melt-extruded under vacuum at a temperature of 160-200℃ (zone one 160℃, zone two 180℃, zone three 190℃, zone four 200℃, die head 195℃) and a screw speed of 300r / min. Finally, the mixture was water-cooled and pelletized to obtain wear-resistant and toughened masterbatch. S6: Under a light-proof, nitrogen atmosphere, 1000g of wear-resistant and toughening masterbatch and 3g of p-hydroxyanisole are added to the main feed port of a twin-screw extruder. 160g of flame-retardant crosslinking agent is added from the first side feed zone, and 12g of photoinitiator 184 and 12g of benzophenone are added from the second side feed zone. Then, melt extrusion is carried out at a temperature of 120℃ in the first zone, 130℃ in the second zone, 145℃ in the third zone, 140℃ in the fourth zone, and 135℃ at the die head, with a screw speed of 200r / min. Finally, the mixture is cooled by water and pelletized to obtain the compound. S7: The compound is vacuum dried at 60℃ for 4 hours, then added to a single-screw extruder. Extrusion is carried out under vacuum and light-proof conditions at a temperature of 125-175℃ (zone 1: 125℃, zone 2: 145℃, zone 3: 165℃, zone 4: 175℃, die head: 170℃) and a screw speed of 60r / min. The molten material is extruded and coated onto the surface of the copper conductor. After cooling and shaping with 30℃ warm water, it is then preheated in a 60℃ preheating tunnel for 15 minutes. Then it is placed on the conveyor belt of an electron beam irradiation device for irradiation treatment with an acceleration voltage of 1.5MeV, an irradiation dose of 120kGy, a conveyor belt speed of 0.5cm / s, and irradiation on both sides 4 times. Finally, it is vacuum treated at 60℃ for 12 hours, then heated to 80℃ at a rate of 5℃ / h and vacuum held for 48 hours. After cooling, wear-resistant and flame-retardant wire is obtained.

[0032] Example 2: A method for preparing a wear-resistant and flame-retardant fabric wire is as follows: S1: Dissolve 347.65 g of hexachlorocyclotriphosphazene in 530 mL of anhydrous tetrahydrofuran. Then, under a nitrogen atmosphere at -3 °C, add a mixed solution of 174 g of allyl alcohol and 334 g of triethylamine dropwise (over 2 hours). React at 0 °C for 6 hours. Filter the solution and distill it under reduced pressure at 25 °C and -0.095 MPa (to remove the solvent and excess allyl alcohol). Then, redissolve the solution in 500 mL of anhydrous tetrahydrofuran. Under a nitrogen atmosphere, add 390.42 g of hydroxyethyl methacrylate and 14.66 g of triethylamine. 4-Dimethylaminopyridine, 334g triethylamine, and 7.45g p-hydroxyanisole were reacted at 30°C in the dark for 19h. After filtration, the solvent was removed by vacuum distillation at 30°C and -0.098MPa. Finally, the mixture was recrystallized four times at 0°C with a mixture of dichloromethane and methanol (volume ratio 10:1) and dried under vacuum at 33°C for 27h to obtain a flame retardant crosslinking agent. S2: 100g of nano-silica was vacuum dried for 12h and then dispersed in 1050mL of anhydrous toluene. After ultrasonic dispersion for 30min under nitrogen atmosphere, 12g of vinyltrimethoxysilane, 8g of 3-methacryloyloxypropyltrimethoxysilane, 1mL of deionized water, and 0.5mL of glacial acetic acid were added and stirred for 25min. Then, the mixture was refluxed at 110℃ for 6.5h (the reflux device was equipped with a water separator to continuously separate the methanol and water generated in the reaction). After centrifugation, the mixture was washed 4 times with anhydrous toluene and vacuum dried to obtain modified silica. S3: Dissolve 2.5g of benzoyl peroxide in 10g of anhydrous toluene to obtain a benzoyl peroxide solution; S4: 40g of maleic anhydride-grafted polyethylene wax and 30g of vinyl-terminated polydimethylsiloxane were dissolved in 800mL of anhydrous toluene and ultrasonically dispersed at 75℃ under a nitrogen atmosphere for 40min. Then, the temperature was raised to 80℃ and 7.5g of benzoyl peroxide solution was added dropwise at 0.2g / h. After reacting at 80℃ for 4.5h, 50g of modified silica was added, followed by 5g of benzoyl peroxide solution added dropwise at 0.1g / h and refluxed for 8h. After centrifugation and washing with hot toluene 4 times, the mixture was vacuum dried to obtain the enhanced microspheres. S5: 1050g of high-density polyethylene resin was vacuum dried at 80℃ for 5h, then mixed with 5.3g of antioxidant 1010, 2.1g of antioxidant 168, and 2.1g of dilauryl thiodipropionate at 3000r / min for 4min. Then, 63g of synergistic microspheres and 9.5g of dipentaerythritol hexaacrylate were added, and the mixture was continued to be kneaded for 2min. The mixture was then fed into a twin-screw extruder, and 9.5g of hydroxymethylpropane trimethacrylate was added in zone two. The mixture was then melt-extruded under vacuum at a temperature of 160-200℃ (zone one 160℃, zone two 180℃, zone three 190℃, zone four 200℃, die head 195℃) and a screw speed of 300r / min. Finally, the mixture was water-cooled and pelletized to obtain the wear-resistant and toughened masterbatch. S6: Under a light-proof, nitrogen atmosphere, 1050g of wear-resistant and toughening masterbatch and 3.2g of p-hydroxyanisole are added to the main feed port of a twin-screw extruder. 168g of flame-retardant crosslinking agent is added from the first side feed zone, and 12.5g of photoinitiator 184 and 12.5g of benzophenone are added from the second side feed zone. Then, melt extrusion is carried out at a temperature of 120℃ in the first zone, 130℃ in the second zone, 145℃ in the third zone, 140℃ in the fourth zone, and 135℃ at the die head, with a screw speed of 200r / min. Finally, the mixture is cooled by water and pelletized to obtain the compound. S7: The compound was vacuum dried at 60℃ for 4.5h, then added to a single-screw extruder and extruded under vacuum and light-proof conditions at a temperature of 125-175℃ (zone 1: 125℃, zone 2: 145℃, zone 3: 165℃, zone 4: 175℃, die head: 170℃) and a screw speed of 60r / min. The molten material was extruded and coated onto the surface of the copper conductor, then cooled and shaped with 35℃ warm water. It was then preheated in a 60℃ preheating tunnel for 15min, and then placed on the conveyor belt of an electron beam irradiation device for irradiation treatment with an accelerating voltage of 1.5MeV, an irradiation dose of 120kGy, a conveyor belt speed of 0.5cm / s, and irradiation on both sides four times each. Finally, it was vacuum treated at 60℃ for 13h, then heated to 80℃ at a rate of 5℃ / h and vacuum held for 49h. After cooling, the wear-resistant and flame-retardant wire was obtained.

[0033] Example 3: A method for preparing a wear-resistant and flame-retardant fabric wire is as follows: S1: Dissolve 347.65 g of hexachlorocyclotriphosphazene in 550 mL of anhydrous tetrahydrofuran. Then, under a nitrogen atmosphere at 0 °C, add a mixed solution of 174 g of allyl alcohol and 334 g of triethylamine dropwise (over 2 h). React at 0 °C for 6 h. Filter the solution and distill it under reduced pressure at 25 °C and -0.095 MPa (to remove the solvent and excess allyl alcohol). Then, redissolve the solution in 500 mL of anhydrous tetrahydrofuran. Under a nitrogen atmosphere, add 390.42 g of hydroxyethyl methacrylate and 14.66 g of triethylamine. 4-Dimethylaminopyridine, 334g triethylamine, and 7.45g p-hydroxyanisole were reacted at 30°C in the dark for 20h. After filtration, the solvent was removed by vacuum distillation at 30°C and -0.098MPa. Finally, the mixture was recrystallized five times at 0°C with a mixture of dichloromethane and methanol (volume ratio 10:1) and dried under vacuum at 35°C for 30h to obtain a flame retardant crosslinking agent. S2: 100g of nano-silica was vacuum dried for 12h and then dispersed in 1100mL of anhydrous toluene. After ultrasonic dispersion for 30min under nitrogen atmosphere, 12g of vinyltrimethoxysilane, 8g of 3-methacryloyloxypropyltrimethoxysilane, 1mL of deionized water, and 0.5mL of glacial acetic acid were added and stirred for 30min. Then, the mixture was refluxed at 110℃ for 7h (the reflux device was equipped with a water separator to continuously separate the methanol and water generated in the reaction). After centrifugation, the mixture was washed 5 times with anhydrous toluene and vacuum dried to obtain modified silica. S3: Dissolve 2.5g of benzoyl peroxide in 12.5g of anhydrous toluene to obtain a benzoyl peroxide solution; S4: 40g of maleic anhydride-grafted polyethylene wax and 30g of vinyl-terminated polydimethylsiloxane were dissolved in 800mL of anhydrous toluene and ultrasonically dispersed at 75℃ under a nitrogen atmosphere for 50min. Then, the temperature was raised to 80℃ and 9g of benzoyl peroxide solution was added dropwise at 0.2g / h. After reacting at 80℃ for 5h, 50g of modified silica was added, and then 6g of benzoyl peroxide solution was added dropwise at 0.1g / h and refluxed for 8h. After centrifugation and washing 5 times with hot toluene, the mixture was vacuum dried to obtain the enhanced microspheres. S5: 1100g of high-density polyethylene resin was vacuum dried at 80℃ for 6h, then mixed with 5.5g of antioxidant 1010, 2.2g of antioxidant 168, and 2.2g of dilauryl thiodipropionate at 3000r / min for 5min. Then, 66g of synergistic microspheres and 10g of pentaerythritol tetraacrylate were added, and the mixture was continued to be kneaded for 2min. The mixture was then fed into a twin-screw extruder, and 10g of hydroxymethylpropane trimethacrylate was added in zone two. The mixture was then melt-extruded under vacuum at a temperature of 160-200℃ (zone one 160℃, zone two 180℃, zone three 190℃, zone four 200℃, die head 195℃) and a screw speed of 300r / min. Finally, the mixture was water-cooled and pelletized to obtain wear-resistant and toughened masterbatch. S6: Under a light-proof, nitrogen atmosphere, 1100g of wear-resistant and toughening masterbatch and 3.4g of p-hydroxyanisole are added to the main feed port of a twin-screw extruder, 175g of flame-retardant crosslinking agent is added from the side feed zone 1, and 13g of photoinitiator 184 and 13g of benzophenone are added from the side feed zone 2. Then, melt extrusion is carried out at a temperature of 120℃ in zone 1, 130℃ in zone 2, 145℃ in zone 3, 140℃ in zone 4, and 135℃ at the die head, with a screw speed of 200r / min. Finally, the mixture is water-cooled and pelletized to obtain the compound. S7: The compound is vacuum dried at 60℃ for 5 hours, then added to a single-screw extruder. Extrusion is carried out under vacuum and light-proof conditions at a temperature of 125-175℃ (zone 1: 125℃, zone 2: 145℃, zone 3: 165℃, zone 4: 175℃, die head: 170℃) and a screw speed of 60r / min. The molten material is extruded and coated onto the surface of the copper conductor. After cooling and shaping with 40℃ warm water, it is then preheated in a 60℃ preheating tunnel for 15 minutes. Then it is placed on the conveyor belt of an electron beam irradiation device for irradiation treatment with an accelerating voltage of 1.5MeV, an irradiation dose of 120kGy, a conveyor belt speed of 0.5cm / s, and irradiation on both sides four times. Finally, it is vacuum treated at 60℃ for 14 hours, then heated to 80℃ at a rate of 5℃ / h and vacuum-held for 50 hours. After cooling, wear-resistant and flame-retardant wire is obtained.

[0034] Comparative Example 1: Compared with Example 1, this comparative example only did not add "enhancing microspheres" in the preparation process of S5. All other steps and parameters were the same, and will not be repeated here. The final result was a wear-resistant and flame-retardant fabric wire.

[0035] Comparative Example 2: Compared with Example 1, this comparative example only replaces the "60g of synergistic microspheres" added in the preparation process of S5 with "25g of modified silica (obtained from S2), 20g of maleic anhydride-grafted polyethylene wax and 15g of vinyl-terminated polydimethylsiloxane". All other steps and parameters are the same, and will not be repeated in this comparative example. Finally, wear-resistant and flame-retardant fabric wires are obtained.

[0036] Comparative Example 3: Compared with Example 1, this comparative example only replaces the "160g flame retardant crosslinking agent" added in the preparation process of S6 with "120g ammonium polyphosphate and 40g melamine". All other steps and parameters are the same, and will not be repeated in this comparative example. Finally, wear-resistant and flame-retardant wires are obtained.

[0037] Comparative Example 4: Compared with Example 1, this comparative example only omits the addition of a "flame retardant crosslinking agent" during the preparation process of S6. All other steps and parameters are the same, and will not be repeated here. The final result is a wear-resistant and flame-retardant electrical wire.

[0038] Performance testing: Determination of flame retardancy: Referring to GB / T 2406.2-2009 standard, the limiting oxygen index (%) of the insulation layer material of the wear-resistant and flame-retardant wires prepared in Examples 1-3 and Comparative Examples 1-4 of this invention was determined, and the results are shown in Table 1.

[0039] Abrasion resistance testing: Referring to GB / T 3960-2016 standard, the insulation material of the wear-resistant and flame-retardant cloth wire prepared in Examples 1-3 and Comparative Examples 1-4 of this invention was made into a sample with a size of 30mm×7mm×6mm and the wear mass (mg) after 1000 revolutions at 100 revolutions per minute under a 5N load was measured. The measurement results are shown in Table 1.

[0040] Crack resistance determination: Referring to GB / T 2951.41-2008 standard, the insulation material of the wear-resistant and flame-retardant cloth wire prepared in Examples 1-3 and Comparative Examples 1-4 of this invention was made into samples with a thickness of 2 mm and a scratch depth of 0.3-0.4 mm. Then, the samples were treated with a 10% volume fraction of nonylphenol polyoxyethylene ether aqueous solution (TX-10) at 50 °C, and the time (h) at any point of the sample when cracking occurred was recorded. The measurement results are shown in Table 1.

[0041] Impact resistance testing: Referring to GB / T 1043.1-2008 standard, the insulation layer material of the wear-resistant and flame-retardant wires prepared in Examples 1-3 and Comparative Examples 1-4 of this invention was tested. The specimens were made into type A notched samples (notch bottom radius 0.25 mm) with dimensions of 80 mm × 10 mm × 4 mm. The impact strength (kJ / m²) under the conditions of 25℃ and pendulum energy of 2.75 J was measured. 2 The measurement results are shown in Table 1.

[0042] Low temperature resistance test: Referring to GB / T 1043.1-2008 standard, the insulation layer material of the wear-resistant and flame-retardant cloth wires prepared in Examples 1-3 and Comparative Examples 1-4 of this invention was measured. The specimens were made into type A notch specimens with a size of 80mm×10mm×4mm (notch bottom radius of 0.25mm). After being stored at -40℃ for 24h, the impact strength retention rate (%) under the conditions of -40℃ and pendulum energy of 2.75J is shown in Table 1.

[0043] Table 1: Performance test results of Examples 1-3 and Comparative Examples 1-4

[0044] Data Analysis: As can be seen from Table 1, the wear-resistant and flame-retardant wire prepared in the embodiments of the present invention has excellent flame retardancy, wear resistance, crack resistance, impact resistance and low temperature resistance.

[0045] The foregoing has provided a detailed description of one embodiment of the present invention, but this description is merely a preferred embodiment and should not be construed as limiting the scope of the invention. All equivalent variations and modifications made within the scope of the claims of this invention should still fall within the patent coverage of this invention.

Claims

1. A wear-resistant and flame-retardant cloth wire, characterized in that, Includes copper conductors and insulating layers; The insulating layer is made of a compound, which includes the following raw materials in parts by weight: 1000-1100 parts of wear-resistant and toughening masterbatch, 3-3.4 parts of p-hydroxyanisole, 160-175 parts of flame-retardant crosslinking agent, 12-13 parts of photoinitiator 184, and 12-13 parts of benzophenone. The wear-resistant and toughening masterbatch comprises the following raw materials in parts by weight: 1000-1100 parts of high-density polyethylene resin, 5-5.5 parts of antioxidant 1010, 2-2.2 parts of antioxidant 168, 2-2.2 parts of dilauryl thiodipropionate, 60-66 parts of synergistic microspheres, 9-10 parts of crosslinking aid, and 9-10 parts of hydroxymethylpropane trimethacrylate; The flame retardant crosslinking agent is prepared from hexachlorocyclotriphosphazene, allyl alcohol, triethylamine, hydroxyethyl methacrylate, 4-dimethylaminopyridine, and p-hydroxyanisole. The enhanced microspheres are prepared by first modifying nano-silica with vinyltrimethoxysilane and 3-methacryloyloxypropyltrimethoxysilane, and then reacting it with maleic anhydride-grafted polyethylene wax and vinyl-terminated polydimethylsiloxane under the initiation of benzoyl peroxide.

2. The wear-resistant and flame-retardant electrical wire according to claim 1, characterized in that, The preparation method of the flame retardant crosslinking agent is as follows: Hexachlorocyclotriphosphazene was dissolved in anhydrous tetrahydrofuran 1, and then a mixed solution of allyl alcohol and triethylamine 1 was added dropwise under a nitrogen atmosphere at -5-0℃. The reaction was carried out at 0℃ for 6 hours, then filtered and the filtrate was distilled under reduced pressure. Subsequently, it was dissolved in anhydrous tetrahydrofuran 2, and then hydroxyethyl methacrylate, 4-dimethylaminopyridine, triethylamine 2, and p-hydroxyanisole were added under a nitrogen atmosphere. The reaction was carried out at 30℃ in the dark for 18-20 hours. After filtration, the filtrate was distilled under reduced pressure, and finally recrystallized and dried to obtain the flame retardant crosslinking agent.

3. The wear-resistant and flame-retardant electrical wire according to claim 2, characterized in that, The ratio of hexachlorocyclotriphosphazene, anhydrous tetrahydrofuran 1, allyl alcohol, triethylamine 1, anhydrous tetrahydrofuran 2, hydroxyethyl methacrylate, 4-dimethylaminopyridine, triethylamine 2, and p-hydroxyanisole is 347.65g: 500-550mL: 174g: 334g: 500mL: 390.42g: 14.66g: 334g: 7.45g.

4. The wear-resistant and flame-retardant electrical wire according to claim 1, characterized in that, The method for preparing the synergistic microspheres is as follows: A1: After vacuum drying, nano-silica is dispersed in anhydrous toluene. After ultrasonic dispersion under nitrogen atmosphere, vinyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, deionized water, and glacial acetic acid are added and stirred for 20-30 min. Then, the mixture is refluxed at 110℃ for 6-7 h. After centrifugation, washing, and drying, modified silica is obtained. A2: Dissolve benzoyl peroxide in anhydrous toluene to obtain a benzoyl peroxide solution; A3: Maleic anhydride-grafted polyethylene wax and vinyl-terminated polydimethylsiloxane were dissolved in anhydrous toluene and ultrasonically dispersed at 75°C under a nitrogen atmosphere. Then, the temperature was raised to 80°C and benzoyl peroxide solution 1 was added dropwise. After reacting at 80°C for 4-5 hours, modified silica was added, followed by the addition of benzoyl peroxide solution 2 and reflux reaction for 8 hours. Finally, the mixture was centrifuged, washed, and dried to obtain enhanced microspheres.

5. The wear-resistant and flame-retardant electrical wire according to claim 4, characterized in that, The ratio of nano-silica, anhydrous toluene, vinyltrimethoxysilane, 3-methacryloyloxypropyltrimethoxysilane, deionized water, and glacial acetic acid in A1 is 100g:1000-1100mL:12g:8g:1mL:0.5mL.

6. The wear-resistant and flame-retardant electrical wire according to claim 4, characterized in that, The mass ratio of benzoyl peroxide to anhydrous toluene in A2 is 2.5:7.5-12.

5.

7. The wear-resistant and flame-retardant electrical wire according to claim 4, characterized in that, The ratio of maleic anhydride-grafted polyethylene wax, vinyl-terminated polydimethylsiloxane, anhydrous toluene, benzoyl peroxide solution 1, modified silica, and benzoyl peroxide solution 2 described in A3 is 40g:30g:800mL:6-9g:50g:4-6g.

8. A method for preparing a wear-resistant and flame-retardant electrical wire according to any one of claims 1-7, characterized in that, Includes the following steps: S1: After vacuum drying of high-density polyethylene resin, it is mixed with antioxidant 1010, antioxidant 168 and dilauryl thiodipropionate for 3-5 minutes. Then, synergistic microspheres and crosslinking aids are added and mixed for 2 minutes. Subsequently, it is added to a twin-screw extruder and hydroxymethyl propane trimethacrylate is added in the second zone. Then, it is melt-extruded under vacuum conditions. Finally, it is water-cooled and pelletized to obtain wear-resistant and toughened masterbatch. S2: Under a light-proof, nitrogen atmosphere, wear-resistant and toughening masterbatch and p-hydroxyanisole are added to the main feed port of the twin-screw extruder, flame retardant crosslinking agent is added from the side feed zone 1, photoinitiator 184 and benzophenone are added from the side feed zone 2, then melt extrusion is carried out, and finally water cooling and pelletizing are performed to obtain the compound. S3: After vacuum drying of the compound, it is extruded and coated onto the surface of the copper conductor under vacuum and light-proof conditions. After cooling and shaping, it is preheated in a 60℃ preheating tunnel for 15 minutes, then irradiated. Finally, it is vacuum treated at 60℃ for 12-14 hours, then vacuum treated at 80℃ for 48-50 hours. After cooling, wear-resistant and flame-retardant wire is obtained.

9. The method for preparing wear-resistant and flame-retardant electrical wire according to claim 8, characterized in that, The crosslinking aid mentioned in S1 is either pentaerythritol tetraacrylate or dipentaerythritol hexaacrylate.

10. The method for preparing wear-resistant and flame-retardant electrical wire according to claim 8, characterized in that, The irradiation treatment described in S3 is as follows: the device is placed on the conveyor belt of an electron beam irradiation equipment and subjected to an accelerating voltage of 1.5 MeV, an irradiation dose of 120 kGy, a conveyor belt speed of 0.5 cm / s, and irradiation on both sides four times.

Citation Information

Patent Citations

  • Flame-retardant extruded insulation low-voltage power cable

    CN121306661A

  • Low-smoke halogen-free environment-friendly power cable

    CN121873456A